Beginning teachers' biographies and coping strategies: An exploratory case study - Knowles, John Gary.; The University of Utah. (1989)
This was an exploratory case study of two beginning secondary school teachers. Teacher biographies are increasingly believed to be important in the socialization process of beginning teachers. The primary objective was to explore the connections between beginning teacher biography and practice in the classroom, particularly as that practice relates to coping strategies and the implications of those strategies in the experiences of two first-year teachers.
The following questions focused the study: (a) How do beginning teachers resolve problems in general life situations and in the classroom? (b) How are beginning teachers' strategies for resolving problems in the classroom modified or impacted by aspects of their personal biographies, and what are the relationships between biographies and coping strategies? and (c) How do the school and classroom contexts modify the beginning teachers' problem-solving strategies and influence or induce their particular coping strategies? The study was conducted over the first 4 months of their teaching, a period in which most individuals move past the most difficult period of their first year. Two women with different backgrounds were selected. One woman found work in an urban, middle-class senior high school, and the other a position in a small, new, semirural junior secondary school. Data collection methods included classroom observations, interviews, and autobiographical journal writings.
Some of the teachers' family were also interviewed. The researcher was the instrument for manipulating the data, and analyses were made using standard ethnographic techniques. The two cases are first presented as stories with minimal analytical interference. The teachers' general problem-solving approaches, used over a lifetime, spilled into the classroom as did their previous thinking about teaching and classrooms. Their idealism, their thinking about teaching, and their images of self-as-teacher were not always easily realized in the classroom because their actions were thwarted by the contexts. Their teaching practices were highly dependent upon their biographies, especially their norms and personal dispositions. Their biographies also had the major influence on the coping strategies that the teachers employed and, together, biography and context interacted in complex ways to profoundly effect their teaching practices.
(UnM)AAI9003877
Source: Dissertation Abstracts International, Volume: 50-09, Section: A, page: 2865.
Chair: Robert V. Bullough.
Thesis (Ph.D.)--The University of Utah, 1989.
Microfiche.
Keywords: Education, Teacher Training; Education, Secondary